Helicobacter pylori Infection Aggravates Dysbiosis of Gut Microbiome in Children With Gastritis - Yang, Lu; Zhang, Jiaming; Xu, Junjie; Wei, Xuxia; Yang, Junjie; Liu, Yi; Li, Hua; Zhao, Changying; Wang, Ying; Zhang, Lei; Gai, Zhongtao (Frontiers in Cellular and Infection Microbiology, 2019)
Introduction:Helicobacter pylori infection consistently leads to chronic and low degree of inflammatory response in gastric mucosa and is closely related with gastrointestinal and extra-gastric diseases. Effects of local microbiome in the stomach have been studied in adults and children with H. pylori infection. It is, however, not known whether the intestinal microbial community differs in children with varying H. pylori infection. The aim of this study is to characterize the altered composition of microbiome induced by H. pylori infection and in gastritis. Materials and Methods: This study involved 154 individuals, including 50 children affected by H. pylori-induced gastritis, 42 children with H. pylori-negative gastritis, and 62 healthy controls. Gut microbiome composition was analyzed using 16S rRNA gene-based pyrosequencing. Fecal bacterial diversity and composition were then compared. Results: On the basis of an analysis of similarities and differences, we found that children with H. pylori-induced gastritis exhibited gut bacteria dysbiosis. The ratio of Firmicutes/Bacteroidetes (F:B) at the phylum level had dramatically decreased in H. pylori-positive gastritis group (HPG) and H. pylori-negative gastritis group (HNG), compared with the healthy control group (HCG). At the family and genus levels, relative abundance of Bacteroidaceae and Enterobacteriaceae was prevalent in HPG and HNG, whereas relative abundance of Lachnospiraceae, Bifidobacteriaceae, and Lactobacillaceae was seen in HCG. Prevalence of different taxa of gut microbiome at the class, order, family, and genus levels was also observed among the three groups. Conclusions: Gastritis can cause changes in composition of fecal microbiome, which is exacerbated by H. pylori infection. These changes in gut microbiome may be related to drug resistance and development of chronic gastrointestinal diseases.